A Primary Epithelioid Sarcoma of the Tongue in a Young Female. (21st September 2018) - Soliman, Mahmoud; Fazeli, Shoreh; Zhao, Qing (Grace)
Abstract: A 23-year-old female with no smoking history or significant medical issues presented with an ulcerated lesion on the ventral surface of the tongue and an underlying firm mass. Histopathological examination of the biopsy revealed an infiltrative and predominantly spindle cell tumor. The initial diagnosis was that of a poorly differentiated carcinoma with sarcomatoid features supported by positive immunostaining for pan cytokeratins (positive for AE1/AE3, Cam5.2, but negative for p40). A partial glossectomy was subsequently performed. The mass lesion was found to involve the full thickness of the anterior two-thirds of the tongue, measuring 1.6 cm in the greatest dimension with surface ulceration. The tumor was composed of both epithelioid and spindle cells with eosinophilic/rhabdoid cytoplasmic changes, with extensive perineural and lymphovascular space invasion. The main differential diagnosis included biphasic synovial sarcoma, angiosarcoma, malignant peripheral nerve sheath tumor, rhabdomyosarcoma, leiomyosarcoma, fibrosarcoma, and epithelioid sarcoma (ES). The immunohistochemical studies showed positive staining of the tumor cells for cytokeratins (AE1/3, cam 5.2, and CK5/6), CD34, CD99, and p16, as well as negative staining for p40, p63, BCL2, CD31, Sox10, desmin, MyoD1, myogenin, and S-100. Of interest, immunostaining for INI-1 was negative, indicating loss of expression. Fluorescent in situ hybridization for SS18-SSX1 fusion was negative, ruling out biphasic synovial sarcoma. The morphology and immunoprofile are consistent with ES, a clinically aggressive sarcoma with 70% recurrence and 50% metastasis. Metastasis was identified in one right level II and one left level III lymph nodes. In the event of no other primary tumor, this lesion mostly likely represents a primary tongue ES. Of the two ES types, the proximal type is faster growing and bodes worse prognosis than the classical type. Proximal epithelioid sarcoma of the tongue is extremely rare. Close follow-up and postsurgical chemoradiation are needed for long-term survival.